Pemahaman fonologi siswa SD terhadap teks muhaddatsah Bahasa Arab - Salsabila, Eva Laily (Maliki Interdisciplinary Journal, 2023)
This study aims to describe phonetic understanding that refers to the pronunciation of language sounds, intonatio ofArabic pronunciation of two students in grade 1 and elementary school. The problem of the study is that there are inaccuracies in the pronunciation of language sounds and intonation when reading Arabic in elementary school students, especially in early grade students. . To solve the problem and the purpose of the study used qualitative methods through observation and interviews. The results of the study proved that (1) the pronunciation of Arabic sounds for grade 1 and grade 6 elementary school students was not perfect. (2) There is an inaccuracy in intonation experienced by grade 1 elementary school students. The understanding of pressure or nabr in grade 5 elementary school has begun to develop, although the resulting intonation is not completely perfect. Based on the results of the study, it can be concluded that the phonetic understanding of elementary school students is not perfect like adults.